2012
DOI: 10.1113/jphysiol.2012.235200
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of prefrontal excitatory neurotransmission by dopamine in the nucleus accumbens core

Abstract: Key points• Dopamine's control over excitatory signals from the cortex to the nucleus accumbens is thought to underlie motor learning, behavioural reinforcement and drug dependence.• In this study, we combined optical recordings of presynaptic release with whole-cell electrophysiology in CB 1 receptor-null mice and bacterial artificial chromosome (BAC) transgenic mice with fluorescently labelled D1 and D2 receptor-expressing neurons to identify the specific interactions between dopamine and glutamate signallin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
103
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(113 citation statements)
references
References 70 publications
(108 reference statements)
8
103
1
1
Order By: Relevance
“…The depression seems to be of presynaptic origin in both cases, because mEPSC frequency, but not amplitude, is reduced (Pennartz et al, 1992;Nicola et al, 1996; but see Ortinski et al, 2012 for effects after withdrawal from cocaine) although no changes in postsynaptic cell parameters are observed (O'Donnell and Grace, 1994). This inhibition is also produced by endogenous dopamine (Harvey and Lacey, 1996;Brady and O'Donnell, 2004) and is observed by washing cocaine or amphetamine directly on the slice (Nicola et al, 1996;Li and Kauer, 2004;Wang et al, 2012). Although evidence indicates that the D1 receptors mediating the inhibition are presynaptic (Pennartz et al, 1992;Nicola et al, 1996;Nicola and Malenka, 1997), it has been suggested that the presynaptic alterations are a consequence of the interaction between postsynaptic D1 receptors and NMDARs, which causes the release of adenosine that affects the presynaptic terminal (Harvey and Lacey, 1997;Chergui and Lacey, 1999;Wang et al, 2012).…”
Section: A Long-term Synaptic Plasticitymentioning
confidence: 99%
See 1 more Smart Citation
“…The depression seems to be of presynaptic origin in both cases, because mEPSC frequency, but not amplitude, is reduced (Pennartz et al, 1992;Nicola et al, 1996; but see Ortinski et al, 2012 for effects after withdrawal from cocaine) although no changes in postsynaptic cell parameters are observed (O'Donnell and Grace, 1994). This inhibition is also produced by endogenous dopamine (Harvey and Lacey, 1996;Brady and O'Donnell, 2004) and is observed by washing cocaine or amphetamine directly on the slice (Nicola et al, 1996;Li and Kauer, 2004;Wang et al, 2012). Although evidence indicates that the D1 receptors mediating the inhibition are presynaptic (Pennartz et al, 1992;Nicola et al, 1996;Nicola and Malenka, 1997), it has been suggested that the presynaptic alterations are a consequence of the interaction between postsynaptic D1 receptors and NMDARs, which causes the release of adenosine that affects the presynaptic terminal (Harvey and Lacey, 1997;Chergui and Lacey, 1999;Wang et al, 2012).…”
Section: A Long-term Synaptic Plasticitymentioning
confidence: 99%
“…This inhibition is also produced by endogenous dopamine (Harvey and Lacey, 1996;Brady and O'Donnell, 2004) and is observed by washing cocaine or amphetamine directly on the slice (Nicola et al, 1996;Li and Kauer, 2004;Wang et al, 2012). Although evidence indicates that the D1 receptors mediating the inhibition are presynaptic (Pennartz et al, 1992;Nicola et al, 1996;Nicola and Malenka, 1997), it has been suggested that the presynaptic alterations are a consequence of the interaction between postsynaptic D1 receptors and NMDARs, which causes the release of adenosine that affects the presynaptic terminal (Harvey and Lacey, 1997;Chergui and Lacey, 1999;Wang et al, 2012). Similarly, D2 receptor-mediated inhibition is thought to include postsynaptic release of eCBs, thereby pointing to a role for postsynaptic D2 receptors .…”
Section: A Long-term Synaptic Plasticitymentioning
confidence: 99%
“…Meanwhile, activation of glutamate receptor increases the dopamine release in the NAc [31]. We also know from the literature that NAc dopamine and glutamate signalling interactions are crucially required in behavioural reinforcement and habit formation and dopamine can modulate excitatory glutamatergic projection from the PFC [82]. The elevation of extracellular dopamine and glutamate levels in the striatum might disrupt Ca 2+ homeostasis leading to the endoplasmic reticulum (ER) stress response [4,72].…”
Section: Effects Of Intra-nac Shell Nmda Administration On Anxiolyticmentioning
confidence: 99%
“…These results may suggest the involvement of the dopamine transmission through D 1 and D 2 receptors of the NAc. Several investigations have suggested the possible dopaminergic and glutamatergic systems interaction in the NAc [66,67] based on which the NAc glutamate transmission is modulated by the dopamine system [37,53,82]. With respect to the interaction of these systems, there is a study showing that the NMDA receptors are localized on the NAc shell neurons which abundantly contain dopamine D 1 receptors [81].…”
Section: Effects Of Intra-nac Shell Nmda Administration On Anxiolyticmentioning
confidence: 99%
“…Presynaptic D1 or nicotinic receptors are present on glutamatergic afferents to hippocampus, entorhinal cortex (EC), prefrontal cortex (PFC), and nucleus accumbens (NAc), as well as afferents to ventral tegmental area (VTA) dopaminergic neurons themselves (Bergson et al 1995;Jones and Wonnacott 2004;Paspalas and Goldman-Rakic 2005;Dumartin et al 2007). The D1 receptors act through adenylyl cyclase and PKA to enhance spontaneous release of glutamate in hippocampus, EC, PFC, NAc, and VTA (Kalivas and Duffy 1995;Bouron and Reuter 1999;Yang 1999;Wang et al 2002Wang et al , 2012. Results in NAc are mixed, and in some cases presynaptic D1 receptors instead decrease glutamatergic transmission (Nicola and Malenka 1998).…”
mentioning
confidence: 99%